Design of an Effective Gas Cleaning Method for a Downdraft Gasifier-Engine-Generator System - Buenaventura, Ramon M.; Manegdeg, Ferdinand G.; Cruz, Ibarra E. (Philippine Engineering Journal; Vol 34 No 2 (2013), 2021)
This paper is an experimental study of the performance of a producer gas cleaning method, including a newly designed oil bath filter, for a rice husk downdraft gasifier-engine-generator system (GEGS). The resulting tar and particulate content is 1.6 mg per m³  of producer gas which enabled a continuous operation of the system for 4 hours, limited only by the ash bin capacity. The system accumulated a total of 105 hours of operation with no harmful effects on the diesel engine as shown by the results of the engine oil analysis. A corresponding systems operations and maintenance procedure was also developed.